2020
DOI: 10.1039/d0cc00512f
|View full text |Cite
|
Sign up to set email alerts
|

Copper-catalyzed cascade cyclization reaction of 3-aminocyclobutenones with electron-deficient internal alkynes: synthesis of fully substituted indoles

Abstract: A novel copper-catalyzed cascade cyclization reaction of 3-aminocyclobutenones with electron-deficient internal alkynes has been developed. This reaction provides a new method for the synthesis of fully substituted indoles by formation of four new bonds and two rings in a single step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…A tentative mechanism is outlined in Scheme An unprecedented cascade cyclization reaction of 3aminocyclobutenones 120 with electron deficient alkynes 121 was investigated by Zhao's group. [92] Notably, the reaction produced fully substituted indoles 122 by formation of two new rings from nonaromatic precursors. Cyclobutenones carrying electro-rich, electron-poor aryl, 1naphthyl, benzyl, alkyl substituents smoothly coupled with various internal alkynes in the presence copper acetate affording corresponding indole derivatives in moderate to excellent yields (43-93 %).…”
Section: Miscellaneous Reactionsmentioning
confidence: 99%
“…A tentative mechanism is outlined in Scheme An unprecedented cascade cyclization reaction of 3aminocyclobutenones 120 with electron deficient alkynes 121 was investigated by Zhao's group. [92] Notably, the reaction produced fully substituted indoles 122 by formation of two new rings from nonaromatic precursors. Cyclobutenones carrying electro-rich, electron-poor aryl, 1naphthyl, benzyl, alkyl substituents smoothly coupled with various internal alkynes in the presence copper acetate affording corresponding indole derivatives in moderate to excellent yields (43-93 %).…”
Section: Miscellaneous Reactionsmentioning
confidence: 99%
“… Similarly, nucleophilic addition of primary arylamines to electron-deficient alkynes afforded active β-enaminones (β-enamino esters), which were also valuable synthetic blocks and reacted further with various dipolarophiles to give versatile nitrogen-containing heterocyclic compounds (eq 2 in Scheme ). In recent years, β-enaminones (β-enamino esters) have founded tremendous applications in the construction of heterocyclic systems due to their easy formation, diverse reactivity, and high atom-economy. On the other hand, nucleophilic addition of N -arylaldimines to electron-deficient alkynes also generated active 1,4-dipoles, which were structurally related to Husigen’s 1,4-dipoles and β-enamino esters. , A literature survey showed that this kind of active 1,4-dipoles mainly reacted with active carbonyl compounds to give the corresponding 1,3-oxazine derivatives. ,, Occasionally, the annulation reaction active CC bond such as arylidene or isatylidene malononitriles to give the corresponding 1,4,5,6-tetrahydropyridine or spiro­[indoline-3,4′-pyridine] derivatives was also reported. , These limited reports revealed that the active 1,4-dipoles generated from the addition reaction of N -arylaldimines to electron-deficient alkynes are potential useful synthons for the construction of various nitrogen-containing heterocycles. In order to further explore their synthetic values and establish the elegant synthetic strategies for diverse nitrogen-containing heterocycles, herein we wish to report the three-component reactions of α , β -unsaturated or normal N -arylaldimines, dialkyl but-2-ynedioates, and 2-arylidene Meldrum acids ( N , N ′-dimethylbarbituric acids) for the convenient construction of functionalized spirocyclic 2,4-dioxa-8-azaspiro[5.5]­undec-9-enes and 2,4,8-triazaspiro[5.5]­undec-9-enes (eq 3 in Scheme ).…”
Section: Introductionmentioning
confidence: 99%